PERSEPSI DAN MOTIVASI MAHASISWA DALAM MEMILIH PROGRAM STUDI PADA JURUSAN PENDIDIKAN BAHASA DAN SENI - Riadi, Bambang (JURNAL PESONA, 2016)
This study aims to describe the perceptions and motivations of students in choosing astudy program at the Department of Language and Art. This is a descriptivequalitative study with a sample size of 50 students. The data were collected throughquestionnaires. The results showed that the students perceptions of the study programin the Department of Language and Arts included are considered good. The studentsperceptions of the quality of study programs, lecturerâ s knowledge, the curriculum ofthe study programs, and the graduate of the study program has been good. However,the students perceptions of infrastructure and tuition fees are still low. The studentâ smotivation in choosing a study program at the Department of Language and Arts fit ineither category. Things that motivate them in choosing a study program at theDepartment of Language and Arts among others: the desire for developing theirinterests and talents, the aspirations to become a teacher, the desire for quicklygetting a job after graduation, the ability to compete with graduates of otheruniversities, the reliance of the knowledge learned can be the foundation of life in thefuture, Unila status as the State Universities, the certification of teachers, the lecturerswho teach have good quality, and the curriculum in the study program fit the workingworld..Keywords: perception, motivation, Department of Language and Art Unila